SILVER DISSOLUTION ON COPPER-BASED ALLOYS - Adorno, A. T.; Beatrice, CRS; Benedetti, Assis Vicente [UNESP]; Cabot, P. L. (Chapman Hall Ltd, 1993)
Electrical resistivity measurements and scanning electron microscopy was used to study the dissolution of silver on Cu-Ag and Cu-Al-Ag alloys. The results seem to indicate that the dissolution temperature is affected by the addition of aluminium.